PENGARUH PENGETAHUAN DAN PEMAHAMAN INVESTASI, MODAL MINIMUM INVESTASI, RETURN, RISIKO DAN MOTIVASI INVESTASI TERHADAP MINAT MAHASISWA BERINVESTASI DI PASAR MODAL (STUDI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS KOTA MALANG) - Nur Aini; Maslichah Maslichah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study aims to determine the effect of knowledge and understanding of investment, minimum capital investment, return, risk and investment motivation towards the interest of students investing in the capital market. The population in this study consisted of 2 universities. The sample used was students of the economics and business faculties of Malang Islamic University and the Islamic State University Maulana Malik. The technique used in sampling is purposive sampling technique, the sample chosen was 92 respondents. Data was taken using the questionnaire method. The data analysis method used is multiple regression analysis with the help of SPSS version 16 software (Product Statistics and Solution Services version 16). The test data used is the simultaneous hypothesis test (f), determination coefficient (R2), and partial hypothesis test (t). The results of the study indicate that simultaneously the independent variables significantly influence the dependent variable. Based on the test results of the coefficient of determination, the adjusted R value is 44.6% while the remaining 55.4% is influenced by other variables not included in this study. Based on the results of partial tests of knowledge and understanding of investment variables does not affect students' interest in investing in the capital market, minimum investment capital does not affect students' interest in investing in the capital market, returns do not affect students' interest in investing in capital markets. capital market, investment motivation does not affect students' interest in investing in the capital market.Keywords: knowledge and understanding of investment, minimum capital investment, return, risk, investment motivation